Rituximab maintenance improves survival in male patients with diffuse large B‐cell lymphoma. Results of the HD2002 prospective multicentre randomized phase III trial. (9th October 2015) - Witzens‐Harig, Mathias; Benner, Axel; McClanahan, Fabienne; Klemmer, Jennifer; Brandt, Julia; Brants, Elke; Rieger, Michael; Meissner, Julia; Hensel, Manfred; Neben, Kai; Dreger, Peter; Lengfelder, Eva; et al.
Summary: In the multicentre prospective randomized HD2002 trial, rituximab maintenance therapy (375 mg/m 2 every 3 months for 2 years) versus observation was evaluated for CD20 + B‐cell lymphoma. Out of 321 patients [161 randomized to the treatment group (TG), 160 to the observation group (OG)], 295 data sets were evaluable for statistical analysis. Estimated 5‐year relapse‐free survival (RFS) was 81% in the TG and 70% in the OG (logrank test, P  = 0·047). In the diffuse large B‐cell lymphoma (DLBCL) subgroup ( n  = 152), 5‐year RFS was excellent, at 87% in the TG and 84% in the OG (logrank test, P  = 0·35). Of note, only in male patients of the DLBCL subgroup was RFS significantly superior in the TG in comparison to the OG (5‐year RFS: 88% vs. 74%; logrank test, P  = 0·05). Cox regression analysis showed a significant interaction between treatment and gender regarding overall survival (OS) ( P  = 0·006) and RFS ( P  = 0·02), with a lower hazard in females than males in the OG [OS: hazard ratio (HR) (female:male) = 0·11; 95% confidence interval (CI) = 0·00–1·03; RFS: HR (female:male) = 0·27; 95% CI = 0·05–0·97], and no significant differences between males and females in the TG. We conclude that Rituximab maintenance therapy improves survival in male patients with DLBCL.